2018
DOI: 10.2525/ecb.56.93
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Analysis of Localized Circadian Arrhythmias in Plant Roots

Abstract: The circadian system in plants is characterized by substantial cellular oscillations over an approximately 24-h period. Interactions between cellular oscillators trigger phase resets near the root meristem, resulting in localized regions of arrhythmic expression of the clock gene CCA1. The arrhythmicity of the circadian rhythm significantly impacts physiologic processes and growth; however, the exact nature of these arrhythmic regions remains unknown. In this study, we analyzed spatiotemporal patterns in CCA1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…Interestingly, in the root, the model predicted a complex spatial pattern, with multiple phase clusters and spatial waves in a single seedling (Fig 5C and S4 Video). These patterns of gene expression were similar to the zig-zag patterns previously reported by others when roots are grown on sucrose supplemented media (16,24,35). We found that these zig-zag patterns emerged with, but not without, local coupling (S5A and S5B Fig).…”
Section: Resultssupporting
confidence: 89%
“…Interestingly, in the root, the model predicted a complex spatial pattern, with multiple phase clusters and spatial waves in a single seedling (Fig 5C and S4 Video). These patterns of gene expression were similar to the zig-zag patterns previously reported by others when roots are grown on sucrose supplemented media (16,24,35). We found that these zig-zag patterns emerged with, but not without, local coupling (S5A and S5B Fig).…”
Section: Resultssupporting
confidence: 89%
“…Interestingly, in the root, the model predicted a complex spatial pattern, with multiple phase clusters and spatial waves in a single seedling ( Fig 5C and S4 Video). These patterns of gene expression were similar to the zigzag patterns previously reported by others, when roots are grown on Coordination of circadian timing in A. thaliana sucrose supplemented media [20,27,46]. We found that these zigzag patterns emerged with, but not without, local coupling (S10 Fig).…”
Section: Local Coupling Limits Desynchrony In the Absence Of Entrainmentsupporting
confidence: 89%
“…In the current study, the size of one pixel in the image is about 230 μm, and time-series data at a certain height are the average of several pixels. The size of cells in the Arabidopsis root is about 10 to 100 μm; therefore, one time-series is the sum of at least 100 cells (Seki et al, 2018). Moreover, phase-dependent response of amplitudes were also observed (Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…The root circadian clock was reset to subjective dusk at the root tip (Fukuda et al, 2012; Voß et al, 2015). Thus, the pattern of secondary root generation may also be related to the spatiotemporal pattern of the circadian clock in plant roots (Seki et al, 2018). Several studies have reported differences in entrainment properties depending on the clock genes (Michael et al, 2003a; Flis et al, 2016).…”
Section: Discussionmentioning
confidence: 99%